Pengaruh Kualitas Pelayanan dan Persepsi Harga terhadap Keputusan Pembelian dengan Minat Beli Sebagai Variabel Intervening pada Pelanggan Counter Dolok Masihul - Syahraini Balqis Al-Husna; Gladiska Alifia Alfatha; Rapat Piter Sony; Willy Cahyadi (JURNAL RISET MANAJEMEN (JURMA), 2026)
The purpose of this study is to determine and analyze the influence of service quality and price perception on purchasing decisions of Dolok Masihul counter customers, both directly and indirectly through purchase intention as an intervening variable. This type of research is explanatory research that explains the causal relationship between variables through hypothesis testing. The sample used in this study was 101 respondents with proportional random sampling technique. The test tool used was Partial Least Square (PLS) using SmartPLS 3.0 software. From the results of this test it can be concluded that service quality does not have a significant effect on purchasing decisions. Price perception does not have a significant effect on purchasing decisions. Purchase intention has a significant effect on purchasing decisions. Service quality does not have a significant effect on purchase intention. Price perception has a significant effect on purchase intention. Service quality does not have a significant effect on purchase decisions through mediation from purchase intention. Price perception has a significant effect on purchase decisions through mediation from purchase intention.